Optimalisasi Optimalisasi Pendekatan Kurikulum Understanding by Design (UbD) Dalam Pembelajaran Abad 21 di SDIT Citra Bangsa: Penelitan Kulitatif di SDIT Citra Bangsa - Novitasari, Afida; Syachruroji, Ahmad; Andriana, Encep (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
Rapid developments and the challenges of the 21st century require the education system to produce students who not only understand the subject matter, but also have critical thinking, communication, collaboration, and creativity (4C) skills. The Understanding by Design (UbD) approach is one solution in designing effective learning that is oriented towards deep understanding. This study aims to describe the optimization of the UbD curriculum approach in 21st century learning at SDIT Citra Bangsa, which includes planning, implementation, results, and obstacles faced. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study show that UbD is applied in a structured and integrated manner in learning activities, focusing on achieving holistic learning objectives and developing 21st century skills. The main obstacles faced are the lack of teacher training and difficulties in compiling authentic assessments. This study recommends improving teacher competence through intensive UbD training and developing evaluation tools that are in accordance with the characteristics of 21st century learning.